Strategi Pemasaran dalam Perspektif Etika Bisnis Islam Studi pada Pengusaha Mebel Desa Potoan Daja, Palengaan, Pamekasan - Zainol Fata (AL-UJRAH, 2024)
Marketing is an activity that is very important in the survival of the company, this is because marketing is an effort to realize company goals, develop business, gain profits and to maintain the viability of the company. Ethics will not be separated in human life. Ethics is nothing but the rules of behavior, human customs in dealing with one another and confirming what is right and what is bad. In making a marketing strategy, ethics must be paid attention to so that the business that will be run does not experience losses. researchers used qualitative research methods. The approach used in this study is a descriptive approach. Primary data and secondary data, the techniques used in data collection are observation, interviews, documentation. Based on the explanation above, it can be concluded that the marketing strategy carried out by furniture entrepreneurs in Potoan Daja Village is a set of marketing tools called the marketing mix to achieve their marketing goals. The marketing mix consists of product, price, promotion and distribution, and an ethical review of the marketing strategy of furniture entrepreneurs in accordance with Islamic business ethics, namely, the products produced are products that are tailored to the demands of consumers. The price set has been agreed upon and adjusted with the entrepreneurs so that there is no price war, the promotion is carried out according to the conditions of the product produced so that nothing is covered up and the distribution is direct distribution by producers to consumers